PENGARUH PEMBERIAN JUS MENGKUDU TERHADAP PENURUNAN HIPERTENSI DI POSYANDU LANSIA KRESNA MUKTI BARATA JAYA SURABAYA - Yobel, Sosilo; C., Donatus Antonius (JURNAL NERS LENTERA, 2017)
Introduction: Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure more than 90 mmHg. Abnormalities in the arteries lead to increased risk of stroke, aneurysm, heart failure, heart attack and kidney damage. Noni is a fruit that many benefits, containing scopoletin, ascorbct acid, xeronin proxeroninase which can lower blood pressure. The purpose of this study was to analyze the influence of mengkudu on the decrease in blood pressure in hypertensive patients at village Krishna Mukti Barata Jaya Surabaya. Methods: This study was pre-experiment designs with one-goup pre-post test design. Independent variable wasnoni and the dependent variable was blood pressure reduction. The sample in this study there were 30 peoples in the Elderly health service posts RW 07 village Krishna Mukti Barata Jaya Surabaya. Sample collection was done by using purposive sampling. The instrument used in data collection is an observation sheet for blood pressure and then analyzed using T-Paired test. Results: Results of T-test result p = 0.000 then α